MUSIC, MYTHS, AND MOUNTAINS: NOMAD AESTHETICS IN KYRGYZSTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Mountains have preserved an outstanding cultural diversity because of their difficult accessibility. Despite high levels of cultural diversity among populations and ethnic groups over short distances, mountain people suffer from isolation, both from one another and from the rest of the world. Cultures can vary tremendously from one mountain valley to another; languages and artistic expressions, such as music and dance, and even entire sets of values and religious belief systems, may differ from one village to another within the same mountain range. In a rapidly globalizing world we must be particularly concerned with protecting cultural diversity, promoting cultural pluralism, and preserving tangible and intangible cultural heritage of mountainous regions. This paper examines the mountain music of Kyrgyzstan and provides us with new insights in which both music and myths help us to understand one of the montane peoples and cultures in Central Asia. This paper also reveals how symbolic meanings and values of mountain music are constituted into what is considered the “Kyrgyz” element in mountain music and it helps to construct a broader understanding of cultural issues concerning ‘music, myths, and mountains.’
Keywords: music; myths; mountains; nomad aesthetics; cultural heritage; Kyrgyzstan